The enforceability of promises in European contract law - Gordley, James (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2001)
Legal experts examine how twelve European legal systems deal with situations where a promise may not be enforceable. Despite differences in legal doctrine, similarities in the results are considered. This is the second completed project of The Common Core of European Private Law launched at the University of Trento.